2008
DOI: 10.1172/jci34378
|View full text |Cite|
|
Sign up to set email alerts
|

In utero supplementation with methyl donors enhances allergic airway disease in mice

Abstract: Asthma is a complex heritable disease that is increasing in prevalence and severity, particularly in developed countries such as the United States, where 11% of the population is affected. The contribution of environmental and genetic factors to this growing epidemic is currently not well understood. We developed the hypothesis, based on previous literature, that changes in DNA methylation resulting in aberrant gene transcription may enhance the risk of developing allergic airway disease. Our findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
212
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(225 citation statements)
references
References 43 publications
(52 reference statements)
7
212
0
6
Order By: Relevance
“…Embryo transfer experiments have revealed that methionine synthase reductase deficiency (necessary for the utilisation of methyl groups from the folate cycle) in mice leads to two distinct, separable phenotypes: adverse effects on their wild-type daughters' uterine environment, leading to growth defects in wild-type grandprogeny, and the appearance of congenital malformations independent of maternal environment that persist for five generations, likely through transgenerational epigenetic inheritance [49]. The data on maternal folate status are less clear, with some evidence that maternal folate supplementation can lead to insulin resistance and transgenerational transmission of respiratory disorders in offspring [50,51]. …”
Section: Mechanismsmentioning
confidence: 99%
“…Embryo transfer experiments have revealed that methionine synthase reductase deficiency (necessary for the utilisation of methyl groups from the folate cycle) in mice leads to two distinct, separable phenotypes: adverse effects on their wild-type daughters' uterine environment, leading to growth defects in wild-type grandprogeny, and the appearance of congenital malformations independent of maternal environment that persist for five generations, likely through transgenerational epigenetic inheritance [49]. The data on maternal folate status are less clear, with some evidence that maternal folate supplementation can lead to insulin resistance and transgenerational transmission of respiratory disorders in offspring [50,51]. …”
Section: Mechanismsmentioning
confidence: 99%
“…Many of these factors have been shown to modify early immune function even in pregnancy, including maternal microbial exposure [20,21], diet [22] and pollutants such as cigarette smoke [23]. Moreover, there is now evidence that these can modify early immune gene expression through potentially heritable epigenetic changes [18,20,24,25,26,27]. Therefore, these have been logical targets for disease prevention strategies.…”
Section: Environmental Targets For Preventionmentioning
confidence: 99%
“…Other immunomodulatory approaches focus on factors which may be causally implicated in the considerable changes in lifestyle, notably factors with both epidemiological associations with allergic disease and evidence of plausible immune mechanisms, including microbial exposure, environmental pollutants and complex dietary changes. Of considerable interest are emerging epigenetic paradigms which provide new perspectives on how these environmental factors may be producing heritable change in gene expression to increase the risk of allergic disease [20,25,33,34,35,36]. …”
Section: Pathways and Target Candidates For Prevention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations